Focusing field induction action on the combination frequency multiplier efficiency - Одаренко, Е. Н. (Radiotekhnika, 2012)
Regularities of the frequency multiplication change under condition of magnetic focusing field induction variation within the framework of the multidimensional model of the nonlinear beam-wave interaction in the combination O-type device with sheet electron beam are investigated. The best value of the normalized cyclotron frequency which corresponds to maximum value of the input frequency transformation factor and physical reasons of the frequency multiplier efficiency enhancement are determined.